Current Account Balance and External Shocks: An Intertemporal Perspective for Post-Bergin and Sheffrin Model (Journal of Asian Development Studies, 2025)
This study is an attempt to investigate the behaviour of CA towards different shocks by using the Post Bergin and Sheffrin present value model of current account (BS-PVMCA). The model has been tested in the context of Pakistan by using the VAR approach covering the time period from 1972 to 2020. The Post BS PVMCA allows the transmission of global shocks through the consumption-based interest rate, which is adjusted for the world interest rate, the exchange rate, and the terms of trade. Based on both formal and informal tests, we concluded that the post-BS PVMCA is consistent with Pakistan's data, as both results are significant. It implies that including the changes in the TOT variable in the BS-PVMCA improves the study's results. Contrary to the existing literature, this study also estimates the individual effects of external and country-specific net output shocks on the CA by decomposing the consumption-based interest rate into its components in the post-BS model. The findings of the study reveal that external shocks play a relatively significant role in determining the CA movements in the case of Pakistan.